Rapid detection of chiral drug ephedrine using erythrosin B for the resonance Rayleigh scattering probe. (31st October 2020) - Zhang, Yuhui; Tan, Xuanping; Wu, Huan; Yang, Jidong
Abstract: Ephedrine (EH) and pseudoephedrine (PEH), which are chiral enantiomers commonly used clinically, have different pharmacological actions and treatment effects due to their chiral nature. In the presence of Pd 2+, the reaction system of Ery B (erythrosin B)‐Pd 2+ has a strong resonance Rayleigh scattering (RRS) intensity. Adding EH into this system reduced the RRS intensity, but PEH could not produce this phenomenon. The chiral recognition of these enantiomers could be achieved according to this spectral difference. At the same time, reduction in RRS strength of the reaction system is proportional to the concentration of EH. Under optimized conditions, the linear range is 40–960 ng/ml, and the detection limit is 3.9 ng/ml. A new method for the rapid detection of EH enantiomers can be established. Based on this assay, a new method for the determination of the chiral enantiomers of EH and PEH can be developed. Abstract : When Pd 2+ was introduced into the Ery B system, the RRS intensity was enhanced significantly. But when EH was introduced into the Ery B‐Pd 2+ system, the RRS intensity was greatly reduced. The RRS decrease in intensity of the Ery B‐Pd 2+ ‐EH system was directly proportional to the ephedrine concentration within a certain range. Therefore, a rapid method for determination of ephedrine could be developed based on RRS decrease. This new analytical method exhibited a good selectivity for detecting Ephedrine.